2014
DOI: 10.1007/s00228-014-1780-0
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing elderly pharmacotherapy: polypharmacy vs. undertreatment. Are these two concepts related?

Abstract: Our findings show high rates of polypharmacy and PPO, as well as a clear relationship between these two concepts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
55
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(65 citation statements)
references
References 58 publications
8
55
0
2
Order By: Relevance
“…The criteria, along with other available explicit criteria, is also criticized by the conflicting evidence of whether their application can achieve objective and measurable improvements in clinical outcomes and prevent possible drug-related adverse events [20,22,[42][43][44][45][46].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The criteria, along with other available explicit criteria, is also criticized by the conflicting evidence of whether their application can achieve objective and measurable improvements in clinical outcomes and prevent possible drug-related adverse events [20,22,[42][43][44][45][46].…”
Section: Discussionmentioning
confidence: 98%
“…A more recent study conducted in Spain revealed that the 2012 Beers criteria detected the highest number of PIMs (44 %) when compared to the 2003 Beers and the 2008 STOPP-START criteria (24.3 and 35.4 %, respectively) [22].…”
mentioning
confidence: 98%
“…An association has been demonstrated between polypharmacy (using ≥ five medications concomitantly) and underprescribing [27], so the high rate of concurrent PIMs and PPOs is not unexpected.…”
Section: Discussionmentioning
confidence: 99%
“…Compliance with recommendations based on START.v1 criteria, while highly variable, is overall low [12]. When the exact reasons for this variability are still unclear, in some instances, the reasons may be low or conflicting with scientific evidence in old complex patients [13][14][15], controversy of preventive medicine in such population [16], or the fear of polypharmacy [17].…”
Section: Introductionmentioning
confidence: 99%